Desenvolvimento e caracterização de um adesivo epóxi nanomodificado e avaliação de desempenho das juntas adesivadas - Mílvia Oliveira dos Reis (2022)
Mechanical and thermal properties of CNT-epoxy at different MWCNT weight percentages (0%, 0,1%, 0,25%, 0,5% and 1,0%) were investigated. The dispersion of the MWCNT in an epoxy adhesive commonly used in an automotive application was performed using a grease worker. This device has a perforated plate, able to produce mechanical shear. To investigate the behaviour of adhesive-CNT mixtures and the bonding performance, four groups were prepared using two different perforates plates, P1 and P2. All nanocomposites were submitted to extreme environmental conditions, resumed as reference (non-aged), 500 h at 100ºC, 500 h at 95% of relative humidity at 40ºC, and 500 h under salt spray. A reduction in glass transition temperature was observed with the addition of the nanofiller and no increases on statistic heat-resistant index temperature were noticed in nanocomposites produced using both plates. Changes in the peaks at 3300 cm-1, 1510 cm-1 and 835 cm-1 after aging were seen in FT-IR spectra. The MWCNT addition to pure epoxy increased the apparent shear strength by 14% using P1. In P2, which has the mechanical shear greater by a factor of 2, no significant differences were observed, due to defects and agglomeration of MWCNTs observed by image analysis.